Magic hypercube and index of welfare and sustainability - Neantro Saavedra-Rivano; Joanilio Rodolpho Teixeira (EconomiA, 2017)
This paper systematically surveys the use of different approaches for the magic square (MS) as an indicator of welfare, a formal system of necessary relations to deal with conflicts of socioeconomic objectives. The starting point is the article of Kaldor (1971) followed by contributions by the OECD from the 1970's resulting in a diagram which allowed a visual diagnosis of macroeconomic performance. Such representations were re-examined by Medrano-B and Teixeira (2013), who introduced a required normalization of the variables. Here, we show that this approach was marred by an oversight, namely the issue of the ordering of variables along the axes. In order to avoid this problem, we propose the use of a new mathematical approach involving a Hypercube Graph, which we call magic hypercube, which produces the same index, regardless the ordering of the variables. An application of the new concept is offered using economic data from Brazil and Chile. – – Este artigo pesquisa de maneira sistemática autilizaç\~ao de diferentes abordagens para o Quadrado Mágico,um indicador de bem-estar que cria um sistema formal de relaç\~oes necessárias para lidar com conflitos de objetivos socioeconômicos. O ponto de partida é o artigo de Kaldor (1971), seguido das contribuiç\~oes da OCDE a partir da década de 1970, resultando num diagrama que permitiu um diagnóstico visual do desempenho macroeconómico. Tais representaç\~oes foram reexaminadas por Medrano-B e Teixeira (2013), que introduziram uma normalizaç\~ao necessária das variáveis. Mostramos que essa abordagem foi prejudicada por um descuido, ou seja, a quest\~ao da ordenaç\~ao de variáveis ao longo dos eixos. Para contornar este problema, propomos o uso de uma nova abordagem matemática envolvendo um Gráfico de Hipercubo, que denominamos Hipercubo Mágico, que produz o mesmo índice, independentemente da ordenaç\~ao das variáveis. Uma aplicaç\~ao do novo conceito é dada usando dados econômicos do Brasil e do Chile.
Keywords: F34; G01; G18; E12; 330; Magical square; Index; Hypercube